2015
DOI: 10.1111/ajgw.12192
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the ability of wine experts and novices to identify odorant signals: a new insight in wine expertise

Abstract: Background and Aims The ability to identify odours is important in wine tasting. Contradictory results have emerged from studies comparing the olfactory identification ability of experts and novices. The aim of this study is to extend the characterisation of olfactory capacity of wine professionals and to discuss the effect of practice and training on odour identification. Methods and Results We used an original method to explore odour identification as a function of a semantic and perceptual task: visual imag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…On the one hand, there are studies suggesting wine experts might have an advantage over novices in how they communicate about wines. Wine experts appear to agree with each other more about how to name wine-related odors than novices or intermediate wine students [ 37 , 41 43 ]. Some studies have also found expert descriptions are more often matched to the correct wine than descriptions composed by novices [ 34 , 35 , 44 ].…”
Section: Introductionmentioning
confidence: 99%
“…On the one hand, there are studies suggesting wine experts might have an advantage over novices in how they communicate about wines. Wine experts appear to agree with each other more about how to name wine-related odors than novices or intermediate wine students [ 37 , 41 43 ]. Some studies have also found expert descriptions are more often matched to the correct wine than descriptions composed by novices [ 34 , 35 , 44 ].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly,Tempere, Hamtat, de Revel, and Sicard (2016) found that wine experts took significantly longer to complete tasks than did novices.…”
mentioning
confidence: 99%
“…Furthermore, we did not control for the levels of wine expertise, although all participants were self-identified wine novices. Wine novices might make less consistent ratings when it comes to wine compared to wine experts (Tempere et al, 2016). Another limitation with the design of the present study was that the silent condition was always presented first, so when participants experienced the soundtrack conditions they had already tasted the wine on one previous occasion (even if they might not have known that it was the same wine).…”
Section: Discussionmentioning
confidence: 96%